International Approach to Environmental and Lung Health. A Perspective from the Fogarty International Center - Glass, Roger I. (Ann Am Thorac Soc, 2018)
The global burden of lung disease is substantial, accounting for an estimated 7.5 million deaths per year, approximately 14% of annual deaths worldwide. The prime illnesses include, in descending order, chronic obstructive pulmonary disease, lung cancer, tuberculosis, acute respiratory infections, asthma, and interstitial lung fibrosis. Key risk factors include smoking, both indoor and outdoor air pollution, and occupational exposures. Although the distribution of both the diseases and the risk factors varies greatly by age, geography, and setting, the greatest burden falls on populations living in low- and middle-income countries. Improvements in these metrics will require major public health interventions to curb smoking; improving air quality both in the community and the household; addressing the ever-present burden of infections, including tuberculosis, flu, and the many agents that cause acute respiratory disease; and identifying and protecting workers from the hazards of exposure to toxic substances. Although research over the years has identified many ways to reduce or prevent the enormous burden of disease, a huge gap exists between what we know and what we can do. This “implementation gap” is the greatest challenge we face in this field today. Research on how best to address and implement the changes needed will require not only biomedical advances to improve treatment but also social, economic, and policy research. We still need to elaborate more effective evidence-based policies and interventions to control tobacco use, address ambient and household air pollution, and improve the prevention and treatment of tuberculosis and acute respiratory infections with vaccines and drugs and reduce exposures to environmental and occupational hazards. Until these efforts receive greater prioritization, the burden of disease is unlikely to diminish a great deal more.